Development and validation of a dementia risk score in the UK Biobank and Whitehall II Cohorts - Anatürk, M; Patel, R; Ebmeier, KP; Georgiopoulos, G; Newby, D; Topiwala, A; de Lange, A-MG; Cole, JH; Jansen, MG; Singh-Manoux, A; Kivimäki, M; Suri, S (BMJ Publishing Group, 2023)
Background Current dementia risk scores have had limited success in consistently identifying at-risk individuals across different ages and geographical locations.